2017
DOI: 10.4103/0366-6999.219157
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Neuropeptide Y Levels in Vasovagal Syncope in Children

Abstract: Background:Vasovagal syncope (VVS) is the most common cause of syncope in children. Neuropeptide Y (NPY) plays an important role in the regulation of blood pressure (BP), as well as myocardial contractility. This study aimed to explore the role of plasma NPY in VVS in children.Methods:Fifty-six children who were diagnosed with VVS (VVS group) using head-up tilt test (HUT) and 31 healthy children who were selected as controls (control group) were enrolled. Plasma NPY concentrations were detected. The independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Baseline SBP, DBP, HR, and QTd were measured in our study. According to previous reports, baseline DBP and HR were significantly lower in the VVS group than in the control group (25), which might be correlated with a deficient circulating volume in VVS patients (26). The relevance between overexcitation of vagal activity and the decreases in baseline HR and BP have also been proposed (27).…”
Section: Discussionmentioning
confidence: 80%
“…Baseline SBP, DBP, HR, and QTd were measured in our study. According to previous reports, baseline DBP and HR were significantly lower in the VVS group than in the control group (25), which might be correlated with a deficient circulating volume in VVS patients (26). The relevance between overexcitation of vagal activity and the decreases in baseline HR and BP have also been proposed (27).…”
Section: Discussionmentioning
confidence: 80%
“…A recent Chinese study showed that the level of NPY in peripheral blood of epileptic children was significantly increased and was positively correlated with NIHSS score and Hamilton Anxiety (HAMA) scores, suggesting that NPY is involved in the onset of epilepsy [ 23 ]. A study by Peking University showed that plasma NPY is significantly reduced in Vasovagal Syncope, which may participate in the pathogenesis of Vasovagal Syncope by increasing total peripheral vascular resistance and reducing cardiac output [ 24 ]. A study in the United States showed that the increased number of monocytes infiltrated into the brain of NPY-deficient mice can aggravate the process of neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between endogenous NPY and tachycardia was found in adults with heart failure, however, whether this correlation is causative or the change in HR is a confounding variable is unknown (Hulting et al, 1990). Contrarily, in children with vasovagal syncope no correlation was found between NPY levels and HR (Liao et al, 2017). NPY has been investigated broadly for its role in many cardiovascular diseases, but regarding its effect on HR in human, further investigation is needed.…”
Section: Neuropeptide Ymentioning
confidence: 99%